Religion, environmental ethics and global climate change - Ahmed Kabashi, Nassereldeen; A. Galal, Fatima (IIUM Press, 2009)
In the past two decades, the global environment and community worldwide has reached great compromise that human activities for government earning more economically are causing changes to the global climate. Increased levels of carbon dioxide (CO2), methane (CH4)' sulphur dioxide (SO2) and other greenhouse gases in the last century have raised temperatures around the planet, as diminishing glaciers, melting icecaps, and record-breaking heat waves support evidence. Records show that surface temperatures have risen about lAO F (0.7 0c) since the early twentieth centuty, and that about 0.9 OF (0.5 0c) of this increase has occurred since 1978. There were some observed changes in oceans, ecosystems, and ice cover are consistent with this warming trend. Unless of course,the mission, vision and ethics are strategies, average global temperatures will probably increase by several degrees Celsius in the next few years, with disastrous environmental consequences: desertification, flood of low-lying coastal areas, an increase in powerful hurricanes, decreased agricultural productivity, and loss of biodiversity. Although there remain some scientific uncertainties and disagreements about the extent of expected temperature increases, the magnitude of the environmental impacts, and how to mitigate global warming, there is now believe that humanity plays a significant role in changing the climate.